Combined effect of damage during installation and long-term mechanical behavior of geosynthetics - Paula, António Miguel (2010)
One of the main questions in using geosynthetics in civil works or ground applications is their durability, in particular, the mechanical actions to which they are subject during the installation processes and construction. Under these actions the geosynthetics can be damaged and the changes in their properties can compromise the performance of the constructions where these materials are used. To contribute to the comprehension on the effect of damage during installation on long-term mechanical behaviour of geosynthetics, a research program was established. Two different geosynthetics have been studied: a woven PP-tape and a woven PE geogrid. These materials have been subjected to field damage tests, using two different soils and two compaction energies. To characterise the effect of the damage induced in the long-term mechanical behaviour, tensile creep tests and creep rupture tests were carried out, according with the procedures described in EN ISO 13431. The results obtained are compared and discussed. The main conclusions of the study are presented.